Sex-Disparity in the Association Between Birthweight and Cardiovascular Parameters in 4-Year-Old Children: A Chinese Cohort Study - Wang, Hualin; Du, Bowen; Wu, Yujian; Li, Zhuoyan; Niu, Yiwei; Ouyang, Fengxiu; Wang, Jian; Chen, Sun; Sun, Kun (Frontiers in Nutrition, 2021)
Background: Sex-related differences in cardiovascular parameters have been well documented in adults. And the impact of birthweight on cardiovascular health in later life has been acknowledged. However, data was limited at an early age regarding the association between birthweight and cardiovascular outcomes, and the sex-disparity in its association remained unclear. Objective: To investigate the association between birthweight and cardiovascular parameters in 4-year-old children. Furthermore, to explore whether sex-disparity existed in this association or higher cardiovascular risk. Methods: Follow-up data from the Shanghai Birth Cohort (SBC) was analyzed. Detailed perinatal information including both maternal and offspring datum were recorded. Blood pressure, echocardiography and anthropometry assessment were conducted at the follow-up of 4-year-old-age. Linear regression models were used to analyze the association between birth weight and left ventricle (LV) structure and function changes in each sex and birthweight category. Sex-specific Multivariable logistic regression models were used to compare risk of left ventricular hypertrophy (LVH) in different birthweight subgroups. Results: Overall, macrosomia was significantly associated with thickened LV posterior wall thickness in systole [LVPWs, (β=0.26, 95% CI: 0.06, 0.45)] and diastole [LVPWd, (β=0.18, 95% CI: 0.06, 0.30)], and thickened interventricular septal thickness in diastole [IVSd, (β=0.16, 95%CI: 0.05, 0.28)]. Boys with macrosomia showed a higher left ventricle mass index [LVMI, (β=1.29, 95%CI: 0.14, 2.43)], thickened LVPWs (β=0.30, 95% CI: 0.05, 0.56) and LVPWd (β=0.21, 95%CI: 0.06, 0.36), and thickened IVSd (β=0.23, 95% CI: 0.09, 0.36). However, no significant association of structural changes in girls was found. Furthermore, an increased risk of LVH was found in macrosomic boys solely (OR=2.79, 95%CI: 1.17, 6.63). Conclusion: Children with macrosomia developed cardiovascular changes as early as 4-year-old age. Macrosomia was associated with LV structural changes and higher LVH risk in pre-school aged boys, while no association was found in girls.